Determinants of Seed Distribution System: The Case of Womberma District, North West Ethiopia - Gizachew Wosene Minwagaw; Wubalem Gobie Ejigu (Advances in Agriculture)
Bread wheat also known as common wheat is one of the most important crops for food security and job opportunities for many smallholders as well as the urban population in Ethiopia. Farmers obtain seed from both formal and informal seed distribution systems. The informal seed sector in the study area is the major supplier of seed for many crops grown in the Womberma district. However, access to the formal seed sector was limited for the farmers. Hence, this study initiated to analyze seed distribution system and determinants of smallholder farmers in selecting seed of bread wheat distribution system in the study areas. The primary data was collected through distributing research questionnaires for the seed distribution systems of bread wheat. The study was based on the data collected from 150 households by using the multistage probability sampling method. The survey result shows that the contribution of public companies for supplying improved bread wheat seed was only 33% whereas 100% of producers confirmed that sources of bread wheat seed were from farm saved and local market which were uncertified leading to production deterioration. In line with these, conducted focus group and key informants confirmed that the major problems of formal seed distribution system were lack of timely supply, price fluctuation, limited quantity, and lack of certified seed suppliers while those of the informal seed distribution system were adulteration, high price, low quality, unable to get the right amount, and lack of timely supply, which concluded that the distribution system was inefficient. The econometrics model was used to analyze determinants of selection in seed distribution system of bread wheat in the study areas. Hence, the result of logit model shows that the level of education, access to credit, household income, extension services, and seed quality significantly and positively influenced farmers’ selection of formal seed distribution system while distance to the nearest seed distribution area influenced negatively the selection of formal seed distribution system in the study areas. Therefore, any concerned bodies should give more attention to establish for farmers formal seed distribution systems of bread wheat seed so as to increase production and productivity of bread wheat in the study areas.